SEXUAL ABUSE TO A CHILD BY A TEACHER (A CRIMINOLOGY RIVIEW) - Nursariani Simatupang (Proceeding International Seminar of Islamic Studies, 2022)
: Children often become victims of sexual abuse. Effect of sexual abuse is fatal, not only for the present but also for its future. The problem is that perpetrators of sexual abuse to a child not only come from ordinary people, but come from various circles including teachers. Teachers who are supposed to educate children to achieve their goals, but they make children as victims. So that, it is necessary to conduct an assessment of sexual abuse to a child by teachers. The research is normative juridical research. The data sources in this research is secondary data. The technique to collecting data is documentation study. Based on the research discovered that sexual abuse to a child is done with the mode of giving the lure and threatening the child. The causes of sexual abuse to a child by teacher are the understanding of children who are lacking and afraid of reporting, weak faith, lack of legal awareness, and low teacher morale.Keywords: Sexual abuse, child, teacher, criminology